Physico-chemical structure of expanded clay concrete properties with complex chemical additive KJ-3 of the “Relaxol” series - N.A, Samigov; S.R, Mazhidov; B.K, Mirzaev; M.U, Karimov (International Journal of Psychosocial Rehabilitation, 2020)
–The article presents the results of a physico-chemical analysis of the cement stone microstructure and processes of hydration changes, crystallization in cement systems, with the complex chemical additive KJ-3 of the “Relaxol” series using infrared spectroscopy, X-ray phase analysis and electron microscopy methodsю It has been established that these additives in cement systems contribute to the creation of new formations crystallizing in a finely dispersed medium, clog capillaries and pores of portland cement stone, compacting and strengthening its structural construction. The content of KJ-3 additive in the composition of expanded clay concrete leads to an increase in its density by 8-10% and prismatic strength by 60% compared with the performance of control samples. At the same time, the complex chemical additive KJ-3 of the “Relaxol” series increases the mobility and frost resistance of expanded clay concrete.